Renormalization of Generalized Quantum Electrodynamics - Bufalo, R. [UNESP] (2015)
In the present work we shall study the renormalizability of Generalized Quantum Electrodynamics (GQED4). The on-shell renormalization scheme is reviewed and applied to the theory and we calculate the explicit expressions for all the counter-terms of the GQED4.